CRABPII和E-FABP在非小细胞肺癌中的表达及其意义 (Zhongguo Fei Ai Za Zhi, 2013)
BACKGROUND AND OBJECTIVE: The cellular retinoic acid-binding protein Ⅱ (CRABPⅡ) and epidermal fatty acid-binding protein (E-FABP) both serving as the transport protein of retinoic acid (RA), through RA signal transduction pathway, commit the cell to opposite fate, apoptosis or survival. The aim of this study is to investigate the expression of CRABPII and E-FABP and significance in non-small cell lung cancer (NSCLC) and their lymph node metastases with tissue microarray technique. METHODS: CRABPII and E-FABP proteins were detected in 54 normal lung tissues, 287 primary NSCLC tissues and 112 lymph node metastatic tissues by SP method of immunohistochemical staining. RESULTS: The expression level of CRABPII in the primary lesions was relevant to the gender of NSCLC patients, the metastasis and TNM staging of NSCLC (P < 0.05), while the expression level of E-FABP was related to the grading and metastasis of NSCLC (P < 0.05). The positive expression rate of E-FABP in NSCLC primary lesion was remarkably higher than that in adjacent normal lung tissues and lymph node metastases, respectively (P < 0.05). The expression level of E-FABP had a recognizable advantage over that of CRABPII in NSCLC primary lesions (P < 0.05). The differential expressions between CRABPII and E-FABP was correlated with the tumor size, grading, metastasis, TNM staging of NSCLC (P < 0.05). The larger the tumor was and the later the TNM staging was, along with cancer metastasis, the more likely the expression of E-FABP would dominate. The expression of CRABPII and difference expression between CRABPII and E-FABP were closely related to the prognosis of NSCLC patients based on Kaplan-Meier survival analysis. CONCLUSION: E-FABP showed high exp ression in NSCLC, and the increased E-FABP expression may involved in the occurrence and development of NSCLC. CRABPII might have a negative effect in NSCLC progression, and its expression was negatively related to the prognosis of NSCLC patients.